Fertility Regulation in Male Rats by Implemented Tetraazamacrocyclic Compounds of Iron(II): Synthetic, Spectroscopic, and Applied Aspects with Toxicological Screening - Ashu Chaudhary; Ran Vir Singh (Bioinorganic Chemistry and Applications)
Antifertility and histopathological investigations were carried out on reproductive organs of male albino rats induced by tetraazamacrocyclic complexes of iron(II). The complexes were synthesized by the template condensation of 1,2-diaminoethane, 1,3-diaminopropane with succinic acid and phthalic acid in 2:2 molar ratios which are abbreviated as [Fe(TAMLn)OAc] (n=1 or 2 and TAMLn represents tetraazamacrocyclic ligand). The complexes have been characterized by elemental analysis, conductivity measurements, IR, and electronic spectra.